5
$\begingroup$

Inspired by this question, I've designed the following series.

$$ \begin{align} S&=\sum_{n=3}^{\infty}\ln\!\left(1+\frac1{2n}\right) \!\ln \!\left(\frac{2n^2+n-6}{2n^2+n-10}\!\right) \tag1 \\\\ T&=\sum_{n=3}^{\infty}(-1)^n\ln\!\left(1+\frac1{2n}\right) \!\ln \!\left(\frac{2n^2+n-6}{2n^2+n-10}\!\right) \tag2 \end{align} $$

Each one admits a nice closed form.

Q1. What are their closed forms?

Q2. To which family would you tell these series belong to ?

$\endgroup$
5
$\begingroup$

Noting that $$ 2n^2+n-6=(n+2)(2n-3),2n^2+n-10=(n-2)(2n+5)$$ one has \begin{eqnarray} S&=&\sum_{n=3}^{\infty}\ln\!\left(1+\frac1{2n}\right) \!\ln \!\left(\frac{2n^2+n-6}{2n^2+n-10}\!\right)\\ &=&\sum_{n=3}^{\infty}\ln\!\left(\frac{2n+1}{2n}\right) \!\ln \!\left(\frac{(n+2)(2n-3)}{(n-2)(2n+5)}\!\right)\\ &=&-\sum_{n=3}^{\infty}\ln\!\left(\frac{2n+1}{2n}\right) \!\ln \!\left(\frac{(2n+5)(2n-4)}{(2n-3)(2n+4)}\!\right)\\ &=&-\sum_{n=3}^{\infty}\ln\!\left(\frac{2n+1}{2n}\right) \!\left(\ln\frac{2n+5}{2n+4}-\ln\frac{2n-3}{2n-4}\right)\\ &=&-\sum_{n=3}^{\infty}\left[\ln\left(\frac{2n+1}{2n}\right) \!\left(\ln\left(\frac{2n+5}{2n+4}\right)-\ln\left(\frac{2n-3}{2n-4}\right)\right)\right]\\ &=&-\sum_{n=3}^{\infty}\left[\ln\left(\frac{2n+5}{2n+4}\right)\ln\left(\frac{2n+1}{2n}\right) -\ln\left(\frac{2n+1}{2n}\right)ln\left(\frac{2n-3}{2n-4}\right)\right]\\ &=&-\bigg[\ln\left(\frac{11}{10}\right)\ln\left(\frac{7}{6}\right)-\ln\left(\frac{7}{6}\right)\ln\left(\frac{3}{2}\right)+\ln\left(\frac{13}{12}\right)\ln\left(\frac{9}{8}\right)-\ln\left(\frac{9}{8}\right)\ln\left(\frac{5}{4}\right)\\ &&+\ln\left(\frac{15}{14}\right)\ln\left(\frac{11}{10}\right)-\ln\left(\frac{11}{10}\right)\ln\left(\frac{7}{6}\right)+\ln\left(\frac{19}{18}\right)\ln\left(\frac{15}{14}\right)-\ln\left(\frac{15}{14}\right)\ln\left(\frac{11}{10}\right)\\ &&+\ln\left(\frac{23}{22}\right)\ln\left(\frac{19}{18}\right)-\ln\left(\frac{19}{18}\right)\ln\left(\frac{15}{14}\right)+\cdots\bigg]\\ &=&\ln\left(\frac{7}{6}\right)\ln\left(\frac{3}{2}\right)+\ln\left(\frac{9}{8}\right)\ln\left(\frac{5}{4}\right). \end{eqnarray} One can use the same way to handle $T$.

$\endgroup$
  • $\begingroup$ Nice answer! (+1) $\endgroup$ – Olivier Oloa Jul 25 '17 at 15:45
  • $\begingroup$ Impressive @xpaul $\endgroup$ – gymbvghjkgkjkhgfkl Aug 13 '17 at 20:59
3
$\begingroup$

Answering Q1.

One has

$$ \sum_{n=3}^{\infty}\ln\!\Big(1+\frac1{2n}\Big) \!\ln \!\left(\!\frac{2n^2+n-6}{2n^2+n-10}\!\right)=\ln\!\Big(\frac32\Big) \!\ln \!\Big(\frac76\Big)+\ln\!\Big(\frac54\Big) \!\ln \!\Big(\frac98\Big). \tag1 $$

Proof. One may write $$ \begin{align} &\sum_{n=3}^{\infty}\ln\!\Big(1+\frac1{2n}\Big) \!\ln \!\left(\!\frac{2n^2+n-6}{2n^2+n-10}\!\right) \\=&\sum_{n=3}^{\infty}\ln\!\Big(1+\frac1{2n}\Big) \!\ln \left[\frac{(2n-3)(n+2)}{(2n+5)(n-2)}\right] \\=&\sum_{n=3}^{\infty}\ln\!\Big(1+\frac1{2n}\Big) \!\ln \!\left[\frac{(2n-3)(2n+4)}{(2n+5)(2n-4)}\right] \\=&\sum_{n=3}^{\infty}\ln\!\Big(1+\frac1{2n}\Big) \!\left[\ln \!\left(\frac{2n-3}{2n-4}\right)-\ln\left(\frac{2n+5}{2n+4}\right)\right] \\=&\sum_{n=3}^{\infty}\ln\!\Big(1+\frac1{2n}\Big) \!\left[\ln \!\left(1+\frac{1}{2(n-2)}\right)-\ln\left(1+\frac{1}{2(n+2)}\right)\right] \\=&\sum_{n=3}^{\infty}\ln\!\Big(1+\frac1{2n}\Big) \!\ln \!\left(1+\frac{1}{2(n-2)}\right)-\sum_{n=3}^{\infty}\ln\!\Big(1+\frac1{2n}\Big)\ln\left(1+\frac{1}{2(n+2)}\right) \\=&\sum_{\color{red}{n=1}}^{\infty}\ln\!\Big(1+\frac1{2(n+2)}\Big) \!\ln \!\left(1+\frac{1}{2n}\right)-\sum_{\color{blue}{n=3}}^{\infty}\ln\!\Big(1+\frac1{2n}\Big)\ln\left(1+\frac{1}{2(n+2)}\right) \\=&\ln\!\Big(\frac32\Big) \!\ln \!\Big(\frac76\Big)+\ln\!\Big(\frac54\Big) \!\ln \!\Big(\frac98\Big), \end{align} $$ where we have made a change of index.

Similarly, one has

$$ \sum_{n=3}^{\infty}(-1)^n\ln\!\Big(1+\frac1{2n}\Big) \!\ln \!\left(\!\frac{2n^2+n-6}{2n^2+n-10}\!\right)=\ln\!\Big(\frac54\Big) \!\ln \!\Big(\frac98\Big)-\ln\!\Big(\frac32\Big) \!\ln \!\Big(\frac76\Big). \tag2 $$

Proof. One may write $$ \begin{align} &\sum_{n=3}^{\infty}(-1)^n\ln\!\Big(1+\frac1{2n}\Big) \!\ln \!\left(\!\frac{2n^2+n-6}{2n^2+n-10}\!\right) \\=&\sum_{n=3}^{\infty}(-1)^n\ln\!\Big(1+\frac1{2n}\Big) \!\ln \left[\frac{(2n-3)(n+2)}{(2n+5)(n-2)}\right] \\=&\sum_{n=3}^{\infty}(-1)^n\ln\!\Big(1+\frac1{2n}\Big) \!\ln \!\left[\frac{(2n-3)(2n+4)}{(2n+5)(2n-4)}\right] \\=&\sum_{n=3}^{\infty}(-1)^n\ln\!\Big(1+\frac1{2n}\Big) \!\left[\ln \!\left(\frac{2n-3}{2n-4}\right)-\ln\left(\frac{2n+5}{2n+4}\right)\right] \\=&\sum_{n=3}^{\infty}(-1)^n\ln\!\Big(1+\frac1{2n}\Big) \!\left[\ln \!\left(1+\frac{1}{2(n-2)}\right)-\ln\left(1+\frac{1}{2(n+2)}\right)\right] \\=&\sum_{n=3}^{\infty}(-1)^n\ln\!\Big(1+\frac1{2n}\Big) \!\ln \!\left(1+\frac{1}{2(n-2)}\right)-\sum_{n=3}^{\infty}(-1)^n\ln\!\Big(1+\frac1{2n}\Big)\ln\left(1+\frac{1}{2(n+2)}\right) \\=&\sum_{\color{red}{n=1}}^{\infty}(-1)^{n+\color{red}{2}}\ln\!\left(1+\frac1{2(n+2)}\right) \!\ln \!\left(1+\frac{1}{2n}\right)-\sum_{\color{blue}{n=3}}^{\infty}(-1)^n\ln\!\left(1+\frac1{2n}\right)\ln\left(1+\frac{1}{2(n+2)}\right) \\=&-\ln\!\Big(\frac32\Big) \!\ln \!\Big(\frac76\Big)+\ln\!\Big(\frac54\Big) \!\ln \!\Big(\frac98\Big), \end{align} $$ where we have made a change of index.

Answering Q2.

The given series are just an instance ($k=1$) of the following family.

Proposition. Let $k=1,2,3,\cdots.$ Then $$ \begin{align} {\small \sum_{n=2k+1}^{\infty}}&{\small \ln\!\left(\!1+\frac1{2n}\!\right) \!\ln \!\left(\!\frac{2n^2+n-8k^2+2k}{2n^2+n-8k^2-2k}\!\right)=\sum_{n=1}^{2k}\ln\!\left(\!1+\frac1{2n}\!\right) \!\ln\!\left(\!1+\frac1{2n+4k}\!\right)}, \tag3 \\\\ {\small \sum_{n=2k+1}^{\infty}(-1)^n} &{\small \ln\!\left(\!1+\frac1{2n}\!\right) \!\ln \!\left(\!\frac{2n^2+n-8k^2+2k}{2n^2+n-8k^2-2k}\!\right)=\sum_{n=1}^{2k}(-1)^n\ln\!\left(\!1+\frac1{2n}\!\right) \!\ln\!\left(\!1+\frac1{2n+4k}\!\right)}. \tag4 \end{align} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.